Case Report: Imaging Features of Gallbladder Sessile Polyp Confirmed by Contrast-Enhanced Ultrasonography and Dynamic Computed Tomography in a Dog With Asymptomatic Chronic Cholecystitis - Lee, Jeongmin; Kang, Jinsu; Heo, Suyoung; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2022)
A six-year-old dog was presented for health screening. It never suffered from any disease. Ultrasonography confirmed mass-like thickening with irregular margins protruding towards the gallbladder (GB) lumen. On contrast enhanced ultrasonography (CEUS) and dynamic computed tomography (CT), contrast enhancement of the corresponding structures were confirmed in arterial phase. After cholecystectomy, cauliflower-like sessile polyps were identified. Histopathological examination revealed chronic lymphoplasmacytic cholecystitis. Bile culture revealed Escherichia coli growth. Our novel findings suggest that chronic cholecystitis should be considered as a differential diagnosis if contrast-enhanced sessile polyps of the GB are found on CEUS and dynamic CT.